2004
DOI: 10.1021/la035370q
|View full text |Cite
|
Sign up to set email alerts
|

Structural Properties of Nonionic Cyclodextrin Colloids in Water

Abstract: The amphiphilic character in water of a novel class of chemically modified cyclodextrins has been investigated by means of small-angle X-ray scattering and light scattering. The introduction ofhydrophilic oligo(ethylene glycol) onto the secondary side of heptakis[6-alkylthio-6-deoxy-2-oligo(ethylene glycol)]-beta-cyclodextrins produces an enhanced water solubility of these molecules. Shape and dimensions of the generated micellar aggregates, analyzed in terms of a suitable core-shell model, remain stable in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
52
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 51 publications
(57 citation statements)
references
References 65 publications
5
52
0
Order By: Relevance
“…A strategy to improve its rate of absorption and to achieve a rapid onset of activity consists in the encapsulation in nanocarriers of ACyDs. It has been shown that specially designed novel classes of amphiphilic b-CyDs are versatile guest encapsulators due to their capability to form micelles, nanoaggregates, 13,15 or vesicles. [12][13][14]26,34 The main peculiarity emerging from this study is the capacity of Gen to interact with SC6OH forming a stable nanosystem prepared with emulsificationdiffusion method.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A strategy to improve its rate of absorption and to achieve a rapid onset of activity consists in the encapsulation in nanocarriers of ACyDs. It has been shown that specially designed novel classes of amphiphilic b-CyDs are versatile guest encapsulators due to their capability to form micelles, nanoaggregates, 13,15 or vesicles. [12][13][14]26,34 The main peculiarity emerging from this study is the capacity of Gen to interact with SC6OH forming a stable nanosystem prepared with emulsificationdiffusion method.…”
Section: Discussionmentioning
confidence: 99%
“…This study was compared with structural properties of analogous systems obtained with conventional method. 15 Furthermore, some preliminary release studies were performed to investigate the potential use of the SC6OH/Gen complex in drug delivery.…”
Section: Introductionmentioning
confidence: 99%
“…The restriction size a decreased with increasing POE-SMO concentration from 1.8 gm at 100 mM to 0.8 ~tm at 300 mM, and it was 0.6 gro for surfactant only. The decrease in the restriction size with increasing POE-SMO concentration suggests that the hydrophilic chains at the surface of micelles may play an important role in order to promote the connectivity between micelles by means of the hydrogen bonds [30].…”
Section: Estimation Of the Hydrodynamic Radius Of A Micellementioning
confidence: 99%
“…More specifically we evidence that spherical porous nanoparticle were formed when the charged terminal groups of the dendrimer irreversibly anchor the zeolite formation to the dendrimer surface. Such selfassembly recently attracted a sensitive attention in material science [11][12][13][14][15] due also for the important implications in the improvement of the models and theoretical approaches describing the relevant assembly mechanism and processes involved in material and life science [16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%